Strategic Planning for University Libraries: The Central Library of Tishreen University is a model (Damascus University Journal of arts and humanities sciences, 2022)
The study aimed at introducing the concept and principles of strategic planning in the university libraries, and shed light on the reality of strategic planning in the central library of Tishreen University. The researcher in his study on the case study methodology using several tools such as the checklist as the main tool, observation and analysis tools of strategic planning the questions included all those directly or indirectly concerned with the administration of the Central Library. The absence of a clear vision to develop future plans to support the library and its services. Based on this, the researcher suggested a comprehensive research strategy based on a set of Arab and international standards as a suggestion to activate it in the central library of Tishreen University.
Keywords: Strategy; Strategic Planning; Management; Planning Methods